Zincophilic–Hydrophobic Interface Design for Dendrite-Free Aqueous Zinc-Ion Batteries - Guo, Yinfeng; Xu, Yuxiang; Jia, Yaduo; Zhu, Xiaoqing; Zhang, Tao; Zhang, Jia; Cao, Changyong Chase; Gu, Qilin; Xu, Guiyin (Nano-Micro Letters, 2026)
Achieving Zn anode stability is critical for advancing commercialization of aqueous zinc-ion batteries. However, the instability of zinc metal anodes driven by dendritic growth, hydrogen evolution, and interfacial passivation remains a critical obstacle for advancing aqueous zinc-ion batteries. In this paper, we report a synergistic interfacial engineering strategy that integrates in situ-grown zincophilic copper nanorod arrays with a self-assembled layer of 1-dodecanethiol to regulate ion flux and suppress side reactions simultaneously. The water-poor electric double-layer microenvironment derived from this dual-function “zincophilic–hydrophobic” architecture (denoted as HS-Cu@Zn) promotes uniform Zn deposition along the (100) plane, enhances desolvation kinetics (Zn2+ transference number increased from 0.47 to 0.75), and effectively excludes electroactive water molecules from the anode surface. As a result, the symmetric cells exhibit ultra-long cycling stability over 3500 h at 1 mA cm−2, while Zn||Cu half-cells maintain a Coulombic efficiency of 99.65% for 900 cycles. ZnVO||HS-Cu@Zn full cell demonstrates exceptional cycling stability, achieving 2000 stable cycles at 5 A g−1 with an average Coulombic efficiency of 99.8%. Highlights: 1 The loose rough surface of the Cu nanorod arrays provided ordered zinc migration channels and was used as a conductive substrate to modulate the nucleation sites of Zn2+, thereby promoting the uniform deposition of Zn2+. 2 The self-assembled layer of thiol molecules effectively reduces the concentration of water molecules at the interface of the Zn anode, ensuring the stability and reversibility of the Zn anode. 3 The synergistic interfacial engineering strategy reduced the desolvation energy of zinc ions and achieved a higher ion transfer number.